After agency: The queer posthumanism of video games that cannot be played. (April 2022) - Ruberg, Bo
This article offers a queer reading of Brent Watanabe's 2016 video game–based art piece San Andreas Deer Cam, a mod of Grand Theft Auto V in which a computer-controlled deer wanders the game's extensive open world. During the time that San Andreas Deer Cam was streamed live on Twitch, it became something of an internet sensation, drawing attention for its comedic elements and the deer's seeming invisibility. I argue here that Watanabe's piece can read in an alternative way: as a work of queer posthumanism. Drawing from game studies scholars whose research explores the non-human (such as Alenda Chang and Paolo Ruffino), as well as queer studies scholars who have theorized how posthumanism challenges norms of gender, sexuality, and intimacy (such as Dana Luciano and Mel Chen), I analyze video recordings of San Andreas Deer Cam. Through these videos, I articulate the piece's posthumanist elements, with a focus on the implications of Watanabe's choice to make the game unplayable and the powerful yet ambivalent picture the piece offers of queerness 'beyond the human'. In San Andreas Deer Cam, queerness manifests in many forms, all of them wrapped up with the messy divide between peoples, animals, and machines: the visual erotics of the deer sensuously rendered backside, moments of sexual misrecognition as non-player characters appear to catcall the deer, even a prolonged scene in which the deer becomes the object of homophobic violence. Ultimately, I conclude, San Andreas Deer Cam offers a model for how video games themselves can be used to rethink the centrality of human agency, which has long been considered the defining feature of the medium. Watanabe's piece serves as a provocation to consider the queer potential of games that are unplayable and of refusing – rather than doggedly pursuing – the supposed capacity of video games to place human players in control.